Charmonium at BESIII - Wu Lianjin (EPJ Web of Conferences, 2019)
With large J/ψ and ψ(2S ) data samples, the BESIII Collaboration has performed many studies toward conventional charmonium states below energy 3.686 GeV, which provide information on the internal structure and the interactions of the mesons. In this proceeding, just a few of them, related to (1) OZI suppressed decay search or measurement, (2) “12% rule” test, and (3) theoretical diﬀerent predictions test, is focused on.